Mental Health Economics : The Costs and Benefits of Psychiatric Care - Razzouk, Denise (Springer International Publishing : Imprint: Springer, 2017)
The main objetive of this book is to provide a high quality content that becomes a reference for graduate courses (Mental Health, Public Health and Epidemiology) and for research in the domain of health economics applied to mental health. Also this book might be useful for policymakers on formulating mental health policies. Key messages of this book are based on: Mental illness represent a huge cost for society and for health care; Health economics applied to mental health could help in the optimization of resource allocation for mental health care and for better decision making in terms of balancing costs and benefits; Interventions and treatment should be also chosen in general medical practice and in public decision-policy according to cost-effectiveness, burden of disease and equity principles; Quality of care is related with better outcomes, higher quality of life for clients, and with lower costs for society and health system; It is possible to decrease the burden of mental disorders with cost-effective treatments. A growing interest in Health Economics applied in mental health has been noticed, especially because mental disorders have been recognized as very costly to society and health care system. However, the majority of books in this topic are oriented mainly to health managers and not for researchers and mental health professionals. There is a need of increasing capacity-building of researchers in this discipline, especially in terms of methods and measurements, and this book aims to fill this gap. Mental Health Economics aims to integrate research methods, quality of clinical interventions, evaluation of quality of care and policymaking in terms of balancing costs and benefits.
Keywords: Medicine.; Public health.; Psychiatry.; Health economics.; Medical economics.; elektronické knihy; electronic books